1998
DOI: 10.1046/j.1365-2125.1998.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol plasma and cerebrospinal fluid pharmacokinetics in children

Abstract: Aims Paracetamol has a central action for both antipyresis and analgesia. Maximum temperature decrease and peak analgesia are reported at 1-2 h after peak plasma paracetamol concentration. We wished to determine the relationship between plasma and cerebrospinal fluid (CSF) pharmacokinetics in children. Methods Concentration-time profiles in plasma and CSF after nasogastric paracetamol 40 mg kg −1 were measured in nine children who had indwelling ventricular drains.Estimation of population pharmacokinetic param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 42 publications
6
67
0
3
Order By: Relevance
“…These events include the pharmacokinetic processes for the drug to be absorbed and to reach the hypothalamus and the pharmacodynamic ones that alter temperature regulation leading to a decrease in heat production and an increase in heat loss. 13 The pharmacokinetic processes may be a limiting factor in rapidly obtaining the expected antipyretic efficacy. It has been shown that the plasma half-life of acetaminophen ranges between 2 and 10 hours in febrile children 5,11,14 ; con- sequently, acetaminophen steady-state plasma concentrations can be reached only approximately between 10 and 50 hours after the first administration.…”
Section: Discussionmentioning
confidence: 99%
“…These events include the pharmacokinetic processes for the drug to be absorbed and to reach the hypothalamus and the pharmacodynamic ones that alter temperature regulation leading to a decrease in heat production and an increase in heat loss. 13 The pharmacokinetic processes may be a limiting factor in rapidly obtaining the expected antipyretic efficacy. It has been shown that the plasma half-life of acetaminophen ranges between 2 and 10 hours in febrile children 5,11,14 ; con- sequently, acetaminophen steady-state plasma concentrations can be reached only approximately between 10 and 50 hours after the first administration.…”
Section: Discussionmentioning
confidence: 99%
“…A tissue:plasma concentration ratio of unity is achieved in all tissues, except fat and cerebrospinal fluid (CSF). At equilibration, the CSF to plasma partition coefficient has been estimated as 1.18 (6,13).…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…The pharmacokinetic parameters of the CSF compartment were estimated. 21 The structural parameters included in the model were the CSF distribution rate constant (k CSF ) and the partition coefficient (PC) corresponding to the ratio of the CSF over the plasma doripenem concentration at steady state. An exponential residual model was used for plasma and CSF concentrations.…”
Section: Pharmacokinetic Modelling and Simulationsmentioning
confidence: 99%